Pengembangan kWh Meter Elektronik untuk Pengecekan CT Konsumen Secara On Site - Fadjar Kurniadi (Energi & Kelistrikan, 2019)
Current Transfomer(CT) accuracy for big customers is very important. Constraints Execution of CT accuracy testing on big customers is quite a lot of customers and scattered, and longtime outage duration. Development of electronic kwh Meter for checking on-site CT customers as a solution to these problems. The onsite CT measurement method is carried out by comparing the primary and secondary of the CT by utilizing the current coil on the electronic kWh Meter. This method has several advantages, lower costs, easy procurement, easy and fast operation, so the duration of outages can be minimized. This method is very supportive in the implementation of the Revenue Assurance program.